Development and test run of civil engineering schedule acceleration model through ant colony optimization - Wang, Chen; Abdul-Rahman, Hamzah; Chow, Pui See (Journal of Civil Engineering and Management, 2016)
The traditional scheduling tool Critical Path Method (CPM) exhibits limitations in computational insufficiency due to exhaustive enumeration. Ant Colony Optimization (ACO) was therefore applied as a metaheuristic inspired by the ants behavior in foraging activities. A model development team was formed among construction engineers, IT professionals, and Mathematicians to develop a schedule acceleration model by integrating ACO into CPM to ensure proper resources allocated on critical path. The developed model CSAM-ACO targets on schedule acceleration by allocating resources on the newly found critical path after two stages of computation. The trial run proved CSAM-ACO model more favorable compared with CPM.First published online: 27 Jan 2016